2020
DOI: 10.1037/xge0000753
|View full text |Cite
|
Sign up to set email alerts
|

Memory’s reflection of learned information value increases across development.

Abstract: Prioritizing memory for the information most likely to be useful in the future is critical to learning effectively in our complex world. Previous work has revealed that the ability to strategically encode high-value information may improve gradually over development, as the systems supporting cognitive control processes mature. However, studies of value-directed memory have relied on explicit cues that signal the importance of information, which are rarely present in realworld contexts. Here, we examined wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 76 publications
5
19
0
Order By: Relevance
“…This effect was modulated by age (χ2(1) = 10.69, p = .001) and quadratic age (χ2(1) = 9.89, p = .002), indicating that participants’ beliefs about item frequency influenced memory to the greatest degree in adolescence and early adulthood. Further, replicating our previous behavioral findings (Nussenbaum et al, 2020), we found that the linear model including explicit frequency reports (BIC = 5417.7) fit the data better than the linear model including the true frequency condition (BIC = 5433.6, χ2 = 15.39, p < .001), indicating that participants’ representations of item frequency influenced memory to a greater extent than the true item frequencies.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…This effect was modulated by age (χ2(1) = 10.69, p = .001) and quadratic age (χ2(1) = 9.89, p = .002), indicating that participants’ beliefs about item frequency influenced memory to the greatest degree in adolescence and early adulthood. Further, replicating our previous behavioral findings (Nussenbaum et al, 2020), we found that the linear model including explicit frequency reports (BIC = 5417.7) fit the data better than the linear model including the true frequency condition (BIC = 5433.6, χ2 = 15.39, p < .001), indicating that participants’ representations of item frequency influenced memory to a greater extent than the true item frequencies.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, prior work suggests that stronger memory traces for constituent components enhances associative memory (Popov & Reder, 2020;Reder et al, 2016). However, in our previous behavioral work (Nussenbaum et al, 2020), we found that removing the relation between item frequency and reward value eliminated the memory benefit for associations involving high-frequency items, suggesting that stimulus familiarity itself did not account for the influence of item frequency on memory in our task. Still, when frequency does predict value, stimulus familiarity may serve as a proxy for information utility.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations